Unlocking Efficient Alkaline Hydrogen Evolution Through Ru–Sn Dual Metal Sites and a Novel Hydroxyl Spillover Effect - Yan, Zhen‐Tong; Tao, Shi; Wang, Juan; Lu, Xiu‐Li; Lu, Tong‐Bu (Advanced materials (Weinheim), 2024)
Alkaline hydrogen evolution reaction (HER) has great potential in practical hydrogen production but is still limited by the lack of active and stable electrocatalysts. Herein, the efficient water dissociation process, fast transfer of adsorbed hydroxyl and optimized hydrogen adsorption are first achieved on a cooperative electrocatalyst, named as Ru–Sn/SnO2 NS, in which the Ru–Sn dual metal sites and SnO2 heterojunction are constructed based on porous Ru nanosheet. The density functional theory (DFT) calculations and in situ infrared spectra suggest that Ru–Sn dual sites can optimize the water dissociation process and hydrogen adsorption, while the existence of SnO2 can induce the unique hydroxyl spillover effect, accelerating the hydroxyl transfer process and avoiding the poison of active sites. As results, Ru–Sn/SnO2 NS display remarkable alkaline HER performance with an extremely low overpotential (12 mV at 10 mA cm−2) and robust stability (650 h), much superior to those of Ru NS (27 mV at 10 mA cm−2 with 90 h stability) and Ru–Sn NS (16 mV at 10 mA cm−2 with 120 h stability). The work sheds new light on designing of efficient alkaline HER electrocatalyst. A Ru–Sn/SnO2 NS electrocatalyst, with optimized Ru–Sn sites for water dissociation and hydrogen adsorption and SnO2‐induced unique hydroxyl spillover, enhances the alkaline hydrogen evolution by accelerating hydroxyl transfer and protecting active sites.